Age of onset of hypertension and risk of dementia in the oldest‐old: The 90+ Study. Issue 2 (16th January 2017) - Corrada, María M.; Hayden, Kathleen M.; Paganini-Hill, Annlia; Bullain, Szofia S.; DeMoss, Jaime; Aguirre, Colette; Brookmeyer, Ron; Kawas, Claudia H.
Abstract: Introduction: We investigated the association between age of onset of hypertension and dementia risk in an oldest‐old cohort. Methods: Participants are from The 90+ Study, a population‐based longitudinal study of people aged 90+ who are survivors from the Leisure World Cohort Study. We estimated hypertension onset age using self‐reported information from The 90+ Study and Leisure World Cohort Study, collected about 20 years earlier. A total of 559 participants without dementia were followed every 6 months for up to 10 years. Results: A total of 224 participants developed dementia during follow‐up (mean = 2.8 years). Compared with those without hypertension, participants whose hypertension onset age was 80 to 89 years had a lower dementia risk (hazard ratio = 0.58, P  = .04) and participants with an onset age of 90+ years had the lowest risk (hazard ratio = 0.37, P  = .004). Discussion: Developing hypertension at older ages may protect against dementia. Understanding the mechanisms for this lower risk is important for determining ways to prevent dementia in the very elderly.